Repeatability of a dynamic sexual trait: Skin color variation in the Brown Booby (Sula leucogaster). (23rd May 2018) - Montoya, Bibiana; Flores, César; Torres, Roxana
Abstract: Individual capacity to invest in a reproductive attempt may change over the breeding season, and such changes may be evaluated by potential partners through signaling mechanisms. Coloration of bare parts, such as exposed skin on the throat (gular skin) or feet, is common among avian species and has the potential to be a dynamic, honest signal of current condition, especially when such coloration is carotenoid-dependent. However, few studies have evaluated the repeatability of dynamic coloration of bare parts in the wild. We determined the presence of carotenoid pigments (lutein, zeaxanthin, 13-cis-beta-carotene, and trans-gamma-carotene) in gular skin samples of male and female Brown Boobies ( Sula leucogaster ) using high performance liquid chromatography (HPLC). We then studied color and perceived color variation in the gular skin of both sexes over the reproductive season, from courtship through parental care. We estimated color using Endler's segment method and perceived color using a tetrahedral color space model. Male and female green chroma was highest during courtship, and, in males, green chroma declined with capture date. Males' perceived greenness (theta) was higher during courtship than during the subsequent reproductive stages, and spectral purity ( r achieved) was higher during courtship than afterward in both sexes. Perceived greenness and spectral purity also decreased with capture date in males. Male and female gular skin color and perceived color across the reproductive cycle showed a repeatability of 17–49%. Hence, the presence of carotenoid pigments in gular skin, the pattern of variation among reproductive stages, and the decline with capture date suggest that, in the Brown Booby, skin color may be costly to maintain, its variation can be perceived by other members of the species, and its intraindividual consistency over time may provide reliable information about individual's quality.